Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.1095-8339.2007.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the taxonomic distinctness of two Geonoma macrostachys (Arecaceae) varieties based on intersimple sequence repeat (ISSR) variation

Abstract: The latest taxonomic account for the palms of the Amazon recognizes two common and widespread varieties of Geonoma macrostachys (Arecaceae) in western Amazonia: acaulis and macrostachys . These varieties are joined by intermediates, which obscure their taxonomic boundaries. An evaluation of the genetic distinctness between G. macrostachys varieties at a local and regional scale is presented. Thirty-one G. macrostachys individuals were randomly sampled from four Peruvian tropical moist forests. Twenty-seven int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…Tomando por base essa definição, podemos observar que a população estudada possui diversidade genética intermediária. Roncal et al (2006) estudando a variabilidade genética de uma população de Geonoma macrostachys Mart. (Arecaeae), por meio de marcadores ISSR, encontraram valores inferiores para diversidade de Nei (0,227) e para o índice de Shannon (0,323), quando comparados com os valores encontrados no presente trabalho.…”
Section: Resultsunclassified
“…Tomando por base essa definição, podemos observar que a população estudada possui diversidade genética intermediária. Roncal et al (2006) estudando a variabilidade genética de uma população de Geonoma macrostachys Mart. (Arecaeae), por meio de marcadores ISSR, encontraram valores inferiores para diversidade de Nei (0,227) e para o índice de Shannon (0,323), quando comparados com os valores encontrados no presente trabalho.…”
Section: Resultsunclassified
“…Additionally, evidence of high allelic variation at SSR loci (short sequence repeat) has been found for Attalea phalerata (Choo et al, 2010), Acrocomia aculeata (Nucci et al, 2008) and Oenocarpus bacaba (Lepsch-Cunha et al, 2003). Exceptions to the pattern of high diversity were reported by McClenaghan & Beauchamp (1986) and Roncal et al (2007). The former research suggested a low allozymic variation in the long-lived Washingtonia filifera that was associated with recent colonization events.…”
Section: Demography and Genetics Of Palm Populationsmentioning
confidence: 88%
“…In this context, estimates of the number of species of palms vary greatly depending on the point of view of the researcher, and some of the past debate over the recognition of palm species has been caused by the paucity and poor quality of available herbarium specimens, which frequently lack informative characters that permit positive identification (Henderson, 1999(Henderson, , 2004Henderson et al, 2008;Roncal et al, 2007). Henderson and Galeano (1996) addressed the status of E. espiritosantensis based on observations from available herbarium specimens, and in their opinion specimens of putative E. espiritosantensis were insufficiently distinct from those of E. edulis to justify recognition of the former.…”
Section: Morphological Species Boundaries and Conservation Biologymentioning
confidence: 99%
“…Hybrid development does not mean that the taxa involved are only one species (Coyne and Orr, 2004). Disagreements over whether local forms should be classified as species, infraspecific taxa or results of natural intraspecific variation have led to varying estimates of species numbers in the palm family (Henderson, 2004;Henderson and Martins, 2002;Roncal et al, 2007). One example of such a taxonomic controversy involves the Euterpe genus.…”
Section: Introductionmentioning
confidence: 97%